Distribution of power output during the cycling stage of a triathlon World Cup - Bernard, T.; Hausswirth, C.; Le Meur, Y.; Bignet, F.; Dorel, S.; Brisswalter, J. (Medicine & Science in Sports & Exercise, 2009)
Purpose: The aim of this study was to evaluate the power output (PO) during the cycle phase of the Beijing World Cup test event of the Olympic triathlon in China 2008.